The Model of Property Tax assessment based on Straight Line Distance and Distance of Travel; Case Study in the West ofBogor City - Hartoyo, harry; S. Damanhur, Didin; Saefuddin, Asep; triguna, gunadi (Badan kebijakan Fiskal, 2014)
The purpose of this study is to find out what factors that affect the land prices, as well as researching the straight line distance or the distance of travel to public facilities stronnger to influence the land prices. The results of this study are necessary to improve the method of determination of the assessment (the value of tax object used by Indonesia's property tax or Nilai Jual Obyek Pajak called NJOP) used in collection all property taxes in the city ofBogor. The data used in this study was 41 vacant lot in area ofBogor Barat, which has been traded throughout the last six months in 2013. Analysis tool used is the Ordinary Least Square (OLS) regression applied to the models of the hedonic price regression (Hedonic Price Method/HPM). Results of the study was the second model uses the distances of travel to public facilities has adjusted R2 of 0.815, is higher than the first model that uses the straight line distance with an adjusted R2 of 0.803, as well as assessment (NJOP) regression to land prices by 0.682. In the second model, five independent variables that affect the land prices are the distances to education facilities, health facilities, security facilities, terminal facilities, and characteristics of the area surrounding the location of the object of research. Adjustment of the determination of the assessment (NJOP), is expected to increase accuracy and fairness, as well as increasing the property tax revenue that results are needed to expand public utilities in the city ofBogor.